Analysis of Changes in the Coastal Dynamics of Watu Gedek and Muara Gede in Lumajang Regency Using Multi-Temporal Satellite Data and Spatial Analysis: Analisis Perubahan Dinamika Garis Pantai Watu Gedek dan Muara Gede Kabupaten Lumajang Menggunakan Data Satelit Multi-Temporal dan Analisis Spasial - Anna Rosytha; Zainal Abidin; Arifien Nursandah Nursandah (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
The southern coastal area of Lumajang Regency experiences high shoreline dynamics due to Indian Ocean waves, ocean currents, river mouth sedimentation, and human activities. Shoreline changes in the form of erosion and accretion affect coastal geomorphology, ecosystem stability, and socio-economic activities. This study aims to analyze shoreline dynamics in the Watu Gedek and Muara Gede areas, Tempursari District, Lumajang Regency, using Landsat imagery from 2020–2025. The methods include shoreline extraction using MNDWI, quantitative analysis with the Digital Shoreline Analysis System (DSAS), and prediction approaches using QSCAT and Random Forest machine learning. The analyzed parameters include NSM, EPR, LRR, and SCE. The results show that erosion dominates approximately ±74% of the transects, with a maximum rate of -11.49 m/year. The most severe erosion occurs in the central segment, while limited accretion occurs in the eastern and western parts with rates up to +2.45 m/year due to local sediment supply. QSCAT and Random Forest results show consistent patterns with DSAS. These findings highlight the importance of adaptive and spatial-data-based coastal management.